2004
DOI: 10.2478/v10050-008-0062-6
|View full text |Cite
|
Sign up to set email alerts
|

Crossing the sea en route to Africa: autumn migration of some Accipitriformes over two Central Mediterranean islands

Abstract: Agostini N., Premuda G., Mellone U., Panuccio M., Logozzo D., Bassi E., Cocchi L. 2004. Crossing the sea en route to Africa: autumn migration of some Accipitriformes over two Central Mediterranean islands. Ring 26, 2: 71-78. Observations were made on the autumn migration of Accipitriformes over the islands of Marettimo and Pantelleria, located between western Sicily and Tunisia (Central Mediterranean). A total of 7451 raptors was counted between 24 August and 12 September 2003, mostly adult Honey Buzzards Pern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…These two routes converge over Turkey and Syria as LSEs travel toward Suez. Few LSEs cross the Mediterranean through the Straits of Gibraltar and via Sicily ( Agostini et al, 2004 ; Onrubia et al, 2011 ; Giordano, 1991 ); these flyways are clearly of minor importance compared with the southeastern flyway.…”
Section: Methodsmentioning
confidence: 99%
“…These two routes converge over Turkey and Syria as LSEs travel toward Suez. Few LSEs cross the Mediterranean through the Straits of Gibraltar and via Sicily ( Agostini et al, 2004 ; Onrubia et al, 2011 ; Giordano, 1991 ); these flyways are clearly of minor importance compared with the southeastern flyway.…”
Section: Methodsmentioning
confidence: 99%
“…In this period, adult Honey Buzzards follow the Italian mainland and northern Sicily concentrating at the Strait of Messina; they reach Africa through the Channel of Sicily, at least part of them via Marettimo and Pantelleria islands, like during spring migration (Fig. 1, Agostini and Logozzo 1997, Agostini et al 2000, Agostini et al 2004b, 2005b. It is interesting to note that adult Honey Buzzards passing via Pantelleria choose the shortest flyway over water to reach Africa, changing their orientation behaviour leaving the island heading WNW.…”
mentioning
confidence: 95%
“…At that time, the Italian population was estimated at 9-13 breeding pairs, and at least 19-22 juveniles were expected to migrate in the three years (Liberatori and Penteriani 2001, Sarà et al 2009. Surveys made at Marettimo reported that all juveniles were migrating in flock with adults, and sometimes in mixed-species flocks with adult European Honey Buzzards Pernis apivorus and Black Kites Milvus migrans (Agostini et al 2000(Agostini et al , 2004. In fact, every year, hundreds of Honey Buzzards and Black Kites migrate in flocks along this route from Western Sicily to Cap Bon (Agostini et al 2000), thus representing a good chance for inexperienced juvenile Egyptian Vultures to find the right path by following them.…”
Section: The Role Of Guidance and Meeting Opportunitiesmentioning
confidence: 99%